Morfometria geométrica de populações subterrâneas e epígeas dos caranguejos de água doce do gênero Aegla Leach 1820, (Crustacea: Anomura: Aeglidae) no Vale do Ribeira, Iporanga, SP - Fernandes, Camile Sorbo (Universidade Federal de São Carlos, 2011)
This study was developed with Aegla species from Parque Estadual Turístico do Alto Ribeira (PETAR) and Parque Estadual Intervales (PEI) areas. The facultative cavernicoles Aegla schmitti and A. marginata are distributed in these areas, as well as the only exclusively subterranean Aeglidae species reported, A. leptochela, A. microphthalma and A. cavernicola. With the purpose of elucidating the influence of the restrictive environmental conditions of the subterranean domain in the troglophiles and, also, the role of extrinsic barriers in distribution and speciation patterns of these crustaceans, we visited epigean and hipogean stream reaches between March 2009 and August 2010. In addition, loans of specimens from the Museu de Zoologia from Universidade de São Paulo (MZUSP) and Laboratório de Estudos de Eglídeos from Universidade de São Paulo (LEEUSP) scientific collections were used. Individuals identified as A. schmitti were analyzed using morphometric geometrics in order to evaluate if this species, rarely registered in caves, establish viable populations in the subterranean environment and, moreover, if shape variations related to adaptations to life in caves were present. The results showed that Santana Cave and Betari River individuals correspond to two distinct morphotypes. These ones are evidences that the species colonize successfully the subterranean environment and, possibly, results from environmentally induced phenotypes or ecotypes selection associated to subterranean environment. Furthermore, it could suggest that the colonization of caves occurs by means of epigean migration, following a metapopulation dynamics with, consequently, transitory subpopulations in some places. The distribution pattern of the species in the studied area allows the conclusion that it depends not only on the absence or presence of extrinsic barriers but, also, on their behaviour and mobility. The absence of individuals in caves previously recorded in the literature could suggest populational decline of Aegla species in the study area. Hence, further ecological studies are needed aiming an effective environmental management and, mainly, the parks inspection.
Keywords: Ecologia; Rochas calcárias; Morfotipos; Troglófilos; CIENCIAS BIOLOGICAS::ECOLOGIA